MiRNA‐encapsulated abiotic materials and biovectors for cutaneous and oral wound healing: Biogenesis, mechanisms, and delivery nanocarriers. Issue 1 (28th June 2022) - Deka Dey, Asmita; Yousefiasl, Satar; Kumar, Arun; Dabbagh Moghaddam, Farnaz; Rahimmanesh, Ilnaz; Samandari, Mohamadmahdi; Jamwal, Sumit; Maleki, Aziz; Mohammadi, Abbas; Rabiee, Navid; Cláudia Paiva‐Santos, Ana; Tamayol, Ali; et al.
Abstract: MicroRNAs (miRNAs) as therapeutic agents have attracted increasing interest in the past decade owing to their significant effectiveness in treating a wide array of ailments. These polymerases II‐derived noncoding RNAs act through post‐transcriptional controlling of different proteins and their allied pathways. Like other areas of medicine, researchers have utilized miRNAs for managing acute and chronic wounds. The increase in the number of patients suffering from either under‐healing or over‐healing wound demonstrates the limited efficacy of the current wound healing strategies and dictates the demands for simpler approaches with greater efficacy. Various miRNA can be designed to induce pathway beneficial for wound healing. However, the proper design of miRNA and its delivery system for wound healing applications are still challenging due to their limited stability and intracellular delivery. Therefore, new miRNAs are required to be identified and their delivery strategy needs to be optimized. In this review, we discuss the diverse roles of miRNAs in various stages of wound healing and provide an insight on the most recent findings in the nanotechnology and biomaterials field, which might offer opportunities for the development of new strategies for this chronic condition. We also highlight the advances in biomaterials and delivery systems, emphasizing their challenges and resolutions for miRNA‐based wound healing. We further review various biovectors (e.g., adenovirus and lentivirus) and abiotic materials such as organic and inorganic nanomaterials, along with dendrimers and scaffolds, as the delivery systems for miRNA‐based wound healing. Finally, challenges and opportunities for translation of miRNA‐based strategies into clinical applications are discussed.